Abnormal Uterine Bleeding Is Associated With Increased BMP7 Expression in Human Endometrium. (May 2017) - Richards, Elliott G.; El-Nashar, Sherif A.; Schoolmeester, John K.; Keeney, Gary L.; Mariani, Andrea; Hopkins, Matthew R.; Dowdy, Sean C.; Daftary, Gaurang S.; Famuyide, Abimbola O.
Abnormal uterine bleeding (AUB), a common health concern of women, is a heterogeneous clinical entity that is traditionally categorized into organic and nonorganic causes. Despite varied pharmacologic treatments, few offer sustained efficacy, as most are empiric, unfocused, and do not directly address underlying dysregulated molecular mechanisms. Characterization of such molecular derangements affords the opportunity to develop and use novel, more successful treatments for AUB. Given its implication in other organ systems, we hypothesized that bone morphogenetic protein (BMP) expression is altered in patients with AUB and hence comprehensively investigated dysregulation of BMP signaling pathways by systematically screening 489 samples from 365 patients for differences in the expression of BMP2, 4, 6, and 7 ligands, BMPR1A and B receptors, and downstream SMAD4, 6, and 7 proteins. Expression analysis was correlated clinically with data abstracted from medical records, including bleeding history, age at procedure, ethnicity, body mass index, hormone treatment, and histological diagnosis of fibroids, polyps, adenomyosis, hyperplasia, and cancer. Expression of BMP7 ligand was significantly increased in patients with AUB (H-score: 18.0 vs 26.7; P < .0001). Patients reporting heavy menstrual bleeding (menorrhagia) as their specific AUB pattern demonstrated significantly higher BMP7 expression. Significantly, no differences in the expression of any other BMP ligands, receptors, or SMAD proteins were observed in this large patient cohort. However, expression of BMPR1A, BMPR1B, and SMAD4 was significantly decreased in cancer compared to benign samples. Our study demonstrates that BMP7 is a promising target for future investigation and pharmacologic treatment of AUB.